Are Aesthetic Preferences Affected by Gender and Age Differences? - Mittheera Leelayudthyothin (Asian Journal of Arts and Culture, 2024)
Aesthetic preferences can be crucial for any brand that considers consumer favorites as essential. Form and shape are the most fundamental design elements concerned for all kinds of products and services. Gender and age differences were the main explanatory variables of interest in this study. The perceptions of two forms comprising representation and geometry associated with two contrary shapes involving solid versus airy, were examined. One hundred and eighty respondents participated by using convenience sampling method. Data collection was obtained through an online questionnaire survey and analyzed by ANOVA statistics. The findings suggested that the representational form is recommended for all ages. All genders appreciate it when it combines with solid shape. In addition, the design of geometric form with airy shape is suggested for LGBTQ and younger clients. The implications in this research offer the insight design guidelines for the use of gender and age differences concerned businesses.
Keywords: Aesthetic Perception and Analysis; Color perception and design